Development of a core outcome set for cardio-oncology (COS-CO) to assess and monitor cancer patients at risk of or with cardiovascular diseases. (2nd July 2022) - Van Den Bussche, K; Von Kemp, B; Manderlier, B; Beeckman, K; Cosyns, B
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): King Baudouin Foundation UZ Brussel Foundation Background: Experts predict a cardio-oncological epidemic in the coming years due to the growing population of cancer survivors, the increasing number of elderly people with chronic cancer therapy, and the high number of cardiovascular diseases resulting from these treatments. Cardio-oncology clinics should provide multidisciplinary, specialised evaluation, and long-term follow-up. Although a number of (inter)national registries for cardio-oncology have been created, international standards for clinical assessment and outcome measurement is lacking. Moreover, patient-reported outcomes tend to be neglected. Purpose: To develop a standard and pragmatic patient-centered outcome set to assess and monitor patients at risk of or with cardiovascular diseases before, during and after oncological treatment. Methods: A list of outcomes and measurement instruments was generated through review of existing registries. The project team reviewed and refined the outcomes prior to starting a Delphi procedure. The panelists, including healthcare providers and researchers were invited to rate the importance of the outcome domains. Results: The set is designed to include all patients within the cardio-oncology clinic, whether before, during or after oncological treatment. We extracted >500 outcomes and after refinement 93 outcomes were rated by the panelists. The set encompass baseline cancer and cardiovascular health status (e.g. risk assessment), treatment variables, and functional, psychosocial, and survival outcomes. Data will be collected through administrative and clinical records, and validated patient-reported outcome measurement instruments. Conclusions: A major component of this set's development was surveying existing registries to establish what measurement efforts are currently being undertaken by health care and research teams. The focus and structure of existing (inter)national cardio-oncology registries limit the extent to which longitudinal patient-centered outcomes can be measured and compared. Due to the underrepresentation of patient-reported outcomes, patients will be interviewed to encompass the patient's perspective. This set aims to facilitate (inter)national comparison in cardio-oncology care, using standardised parameters and meaningful patient-centered outcomes for research and quality of care assessments.